Manajemen Sarana Prasarana Dalam Meningkatkan Kualitas Lembaga Pendidikan - Nasiruddin Nasiruddin; Anis Fauzi; Wahyu Hidaya (Journal on Education, 2024)
Management of educational facilities and infrastructure is a process of cooperation in utilizing all educational infrastructure facilities effectively and efficiently. And this shows that the facilities and infrastructure in schools need to be utilized and managed properly for the benefit of the learning process in educational institutions. Therefore, infrastructure management is very important because without good infrastructure management, an educational institution will not run effectively and efficiently. The problems that will be studied in this study are examining the definition of infrastructure management, the principles of infrastructure management, and the infrastructure management process. The purpose of writing this article is to describe and analyze infrastructure management in improving the quality of educational institutions. The method used in this research is qualitative research with a literature study approach. In the literature study, the author conducts literature collection activities related to infrastructure management in improving the quality of educational institutions. The final result of this study aims to find out the definition of infrastructure management, the principles of infrastructure management, and the infrastructure management process.